STRATEGI DAKWAH SYEKH ABDURRAHMAN BATUHAMPAR BERBASIS SIRAU DI NAGARI BATUHAMPAR LIMA PULUH - Saprijon Saprijon (ADISAM PUBLISHER, 2024)
Based on the background of this research, it was influenced by the da'wah and religious activities carried out by Sheikh Abdurrahman in Batuhampar village, where researchers examined the da'wah strategy of Sheikh Abdurrahman based on surau in Batuhampar village. The purpose of this study was to determine the suaru-based preaching strategy of Sheikh Abdurrahman in Batuhampar village, fifty cities. The qualitative research method with data collection using interviews with the people of nagari batuhampar as sources. The data collection techniques that the authors used were interviews and documentation with the people of nagari batuhampar who were selected as research sources. The data analysis technique that the author uses is data presentation and conclusion drawing. From the results of the study it can be concluded that the da'wah strategy conveyed by Sheikh Abdurrahman used sentimental strategies, because he delivered da'wah by taking the hearts of the community by doing good and polite. Then he inserted Islamic teachings in every community activity in Batuhampar village. Start by changing the habits of the community that are contrary to Islamic teachings